Blueberry Extracts Protect Testis from Hypobaric Hypoxia Induced Oxidative Stress in Rats. (31st October 2012) - Zepeda, Andrea; Aguayo, Luis G.; Fuentealba, Jorge; Figueroa, Carolina; Acevedo, Alejandro; Salgado, Perla; Calaf, Gloria M.; Farías, Jorge
Abstract : Exposure to hypobaric hypoxia causes oxidative damage to male rat reproductive function. The aim of this study was to evaluate the protective effect of a blueberry extract (BB-4) in testis of rats exposed to hypobaric hypoxia. Morphometric analysis, cellular DNA fragmentation, glutathione reductase (GR), and superoxide dismutase (SOD) activities were evaluated. Our results showed that supplementation of BB-4 reduced lipid peroxidation, decreased apoptosis, and increased GR and SOD activities in rat testis under hypobaric hypoxia conditions ( P < 0 . 05 ) . Therefore, this study demonstrates that blueberry extract significantly reduced the harmful effects of oxidative stress caused by hypobaric hypoxia in rat testis by affecting glutathione reductase and superoxide dismutase activities.